Issues in combining continuous assessment scores with external examination scores for certification at the basic and secondary school levels: Issues in combining continuous assessment scores with external examination scores for certification at the basic and secondary school levels (Journal of Educational Management, 2000)
Combining continuous assessment scores with external examination scores for the certification and selection of junior and senior secondary school graduates has gained currency in some countries, including Ghana and Nigeria. While the rationale behind combining continuous assessment scores with external examination scores appears to be sound, there are some fundamental issues which must be understood and addressed by policy makers and practitioners in order to make informed decisions concerning the practice. This paper addresses some relevant issues relating to the policy and practice of combining the two sets of scores for certification. The issues include differences in the quality of teacher assessments and external examinations, methods of moderating teacher assessment scores before combining them with external examination scores and challenges of moderating teacher assessment scores. Some suggestions are made concerning how some of the issues may be resolved.